Practical Aspects of Declarative Languages 14th International Symposium, PADL 2012, Philadelphia, PA, USA, January 23-24, 2012. Proceedings - Russo, Claudio; Zhou, Neng-Fa.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This book constitutes the refereed proceedings of the 14th International Symposium on Practical Aspects of Declarative Languages, PADL 2012, held in Philadelphia, PA, USA, in January 2012, co-located with POPL 2012, the 39th Symposium on Principles of Programming Languages. The 38 revised technical papers presented together with 3 application papers were carefully reviewed and selected from 52 submissions. The volume features original work emphasizing new ideas and approaches pertaining to applications and implementation techniques of declarative languages and addresses topics such as innovative applications of declarative languages, declarative domain-specific languages and applications, practical applications of theoretical results, new language developments and their impact on applications, evaluation of implementation techniques on practical applications, novel implementation techniques relevant to applications, novel uses of declarative languages in the classroom, and practical experiences.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Computer Science; Programming Languages, Compilers, Interpreters; Programming Techniques; Logics and Meanings of Programs; Software Engineering; Mathematical Logic and Formal Languages; Artificial Intelligence (incl. Robotics).